2021
DOI: 10.1051/0004-6361/202038605
|View full text |Cite
|
Sign up to set email alerts
|

The physical properties of local (U)LIRGs: A comparison with nearby early- and late-type galaxies

Abstract: Aims. In order to pinpoint the place of the (ultra-) luminous infrared galaxies ((U)LIRGs) in the local Universe, we examine the properties of a sample of 67 such nearby systems and compare them with those of 268 early- and 542 late-type, well studied, galaxies from the DustPedia database. Methods. We made use of multi-wavelength photometric data (from the ultra-violet to the sub-millimetre), culled from the literature, and the CIGALE spectral energy distribution fitting code to extract the physical parameters… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 107 publications
1
24
0
Order By: Relevance
“…Table 3 gives the set parameters used to build the SEDs of our galaxies. We adopted parameters similar to those used in Małek et al (2017) and Paspaliaris et al (2021) and modified them accordingly to suit the galaxies in the current sample. The SED fitting was performed with a very careful adjustment of the fitting parameters, module by module.…”
Section: Uv To Radio Sed Modeling With Cigalementioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 gives the set parameters used to build the SEDs of our galaxies. We adopted parameters similar to those used in Małek et al (2017) and Paspaliaris et al (2021) and modified them accordingly to suit the galaxies in the current sample. The SED fitting was performed with a very careful adjustment of the fitting parameters, module by module.…”
Section: Uv To Radio Sed Modeling With Cigalementioning
confidence: 99%
“…In Figure 9 we show the relation of SFR IR with dust mass for our sample, including data from the literature for normal starforming galaxies in the Local Universe (da Cunha et al 2010), LIRGs at low (z < 0.5) and high (z > 0.5) redshifts (Vega et al 2008;Lo Faro et al 2013;Pereira-Santaella et al 2015;da Cunha et al 2015;Małek et al 2018;Paspaliaris et al 2021), and ULIRGs at low and high redshifts (Vega et al 2008;da Cunha et al 2015;Małek et al 2017Małek et al , 2018. Our sample of LIRGs lies essentially in between the two sequences of normal and starburst galaxies defined by Rowlands et al (2014), in excellent agreement with the behavior shown by starburst galaxies.…”
Section: Sfr Ir Versus M Dustmentioning
confidence: 99%
See 1 more Smart Citation
“…Viaene et al 2017;Bianchi et al 2018), with the absorption fraction rising up to even ∼ 87 per cent in the special cases of (ultra) luminous infrared galaxies (e.g. Paspaliaris et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hirashita 2012;Draine 2009;Asano et al 2013;Zhukovska 2014;Galliano et al 2018Galliano et al , 2021Granato et al 2021), except at low-metallicity environ-∼ 87% in the special cases of (ultra) luminous infrared galaxies ((U)LIRGs; e.g. Paspaliaris et al 2021).…”
Section: Introductionmentioning
confidence: 99%